Postcranial skeleton of Spalacopus cyanus (Rodentia: Octodontidae): description and functional aspects - Pérez, M. Julieta; Díaz, M. Monica (THERYA, 2020)
The genus Spalacopus includes only one species, S. cyanus, endemic to central Chile and one of the species best adapted to a subterranean lifetyle in the family Octodontidae. It is a member of the lineage consisting in Octodontomys as a sister clade containing Octodon and of a clade represented by Spalacopus and Aconaemys. Although the external and cranio-dental morphology have been well studied, little is known of the postcranial morphology of S. cyanus. Because of the peculiarities of its lifestyle and locomotion among the members of the family, it is interesting to characterize details of the morphology of the postcranial skeleton of this species and to infer their functional aspects of the morphology. Twenty-nine specimens with postcranial material stored in two collections were studied: Museo de La Plata (MLP), La Plata, Buenos Aires, Argentina and Colección de Mamíferos del Instituto de Ciencias Ambientales y Evolutivas (UACH), Universidad Austral de Chile, Valdivia, Chile. To describe in detail the morphology of the bone elements, the skeleton was divided in the following regions: axial skeleton, scapular girdle and forelimb, and pelvis girdle and hindlimb. The structures included in the axial skeleton were mainly described in cranial-caudal orientation and the limbs in proximal-distal orientation. All structures were observed with stereoscopic microscopes Leica Wild M3Z and Nikon SMZ 745T including pictures to illustrate the descriptions. Highly conservative characteristics among members of the family Octodontidae were observed in the postcranial morphology of S. cyanus, although some characters are exclusive to this species. The axial skeleton has seven cervical vertebrae, 12 or 13 thoracic, six or seven lumbar, four sacral, 16 to 18 caudal vertebrae, 12 or 13 ribs and a sternum with five sternebrae. The elements of the scapular and pelvic girdles as well as forelimbs and hindlimbs are described in detail, except the carpus and tarsus due to their poor state of conservation, or because they not available. The morphological pattern observed in the postcranial skeleton of S. cyanus conforms to a typical anatomical plan for terrestrial species, and some bones (mainly humerus and ulna) present characteristics associated with digging. The information obtained provided will allow a better interpretation of the postcranial attributes, functionally related with different lifestyle, in a future, as well as the evolution of the traits in a phylogenetic context.